Squamous Metaplasia in a Borderline Phyllodes Tumor—an Undocumented Histological Finding in Male Breast: Report of a Case and Review of Literature. (February 2022) - Panigrahi, Chinmayee; Jha, Shilpy; Kumar, Pankaj; Mishra, Tushar S.; Sasmal, Prakash K.; Adhya, Amit K.
Phyllodes tumor is a paradigm of fibroepithelial neoplasm that accounts for <1% of the breast neoplastic lesions usually detected in females and uncommonly in the male breast. The World Health Organization classifies the tumor into benign, borderline, and malignant based on the predefined morphological criteria. Squamous differentiation in phyllodes tumor is epithelial metaplasia, which has been occasionally documented in English literature. We report the first undocumented case of a recurrent borderline phyllodes tumor with cystic squamous metaplastic change in a 32-year-old male patient. The histology was that of a fibroepithelial neoplasm with the typical leaf-like projections and cystic spaces lined by squamous epithelium containing keratin debris. The purpose of presenting this case is to elucidate the pathogenesis and discuss other malignant and benign breast lesions that may be included in the differential diagnosis when evaluating a breast lesion with squamous metaplasia, particularly in the context of fine-needle aspirates.